2021
DOI: 10.1186/s12866-021-02327-7
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota changes in preeclampsia, abnormal placental growth and healthy pregnant women

Abstract: Background Preeclampsia (PE) is a condition of high blood pressure that is usually concurrent with proteinuria in pregnancy. PE complicates the management of both maternal and fetal health and contributes to most adverse pregnancy outcomes, but the mechanism underlying the development of PE remains unclear. In this study, we performed a case-control study to compare the gut microbiota of PE (n = 26), abnormal placental growth (APG, n = 25) and healthy pregnant women (n = 28) and analyzed the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 49 publications
(64 reference statements)
1
24
0
Order By: Relevance
“…A number of observational studies have reported the association between gut microbiota and PE [ 16 19 , 43 46 ]. Bifidobacterium was found to be associated with a lower risk of PE, which is consistent with the results of our study [ 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of observational studies have reported the association between gut microbiota and PE [ 16 19 , 43 46 ]. Bifidobacterium was found to be associated with a lower risk of PE, which is consistent with the results of our study [ 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to significant pathogenetic heterogeneity, no reliable biomarkers or clinical trials could predict the occurrence of PE during early pregnancy. Moreover, timely termination of pregnancy is the only effective treatment of PE to date, highlighting the significance of early diagnosis and treatment for improving the prognosis of PE (5). The International Federation of Gynecology and Obstetrics (FIGO) suggested that maternal risk factors, including maternal age, obesity, and family history along with biomarkers, could efficiently predict the risk of PE.…”
Section: Introductionmentioning
confidence: 99%
“…Sterile sampling of the human placenta is difficult to obtain. Leiby et al also suspected that the evidence for the existence of the placental microbiome is not scientifically reliable [ 40 ]. To be able to test it, it would be necessary to develop a method of collecting the material that does not raise ethical dilemmas and is carried out in sterile conditions, eliminating the possibility of pre-laboratory errors [ 41 ].…”
Section: Possible Beginning Of the Formation Of The Intestinal Microb...mentioning
confidence: 99%
“…In a study of 100 women, 26 were pregnant with preeclampsia, 25 had abnormal growth of the placenta, 21 were healthy non-pregnant women, and 28 were healthy pregnant women. A significant reduction in the abundance of Prevotella, Porphyromonas, Varibaculum, and Lactobacillus was observed in women with preeclampsia compared to pregnant women without this complication [ 40 ]. Prevotella is a bacterium that exerts many functions in the human gastrointestinal tract [ 48 ].…”
Section: Gut Microbiome and Preeclampsiamentioning
confidence: 99%
See 1 more Smart Citation